Venous extravasation and polymethylmethacrylate pulmonary embolism following fluoroscopy-guided percutaneous vertebroplasty - Makary, Mina S (Acta Radiol Open, 2015)
Percutaneous vertebroplasty has gained widespread popularity and demonstrated clinical efficacy in the treatment of spinal osteoporotic compression fractures and pathologic osteolytic lesions. Despite its rapid pain relief and safety, this minimally invasive intervention has exhibited some rare complications over the past decade. In this case study, we describe a patient with an uncommon complication of polymethylmethacrylate (PMMA) cement pulmonary embolism following fluoroscopy-guided percutaneous vertebroplasty for treatment of pain associated with an osteoporotic vertebral fracture. We present this case to highlight that vertebroplasty is not risk-free and that knowledge of such potentially severe complication is necessary for prevention and optimal operative outcomes.